E-Waste trading zones and the economy of greening: Imbricating computer sourcing in the pre- and post-WEEE Directive era. Issue 2 (28th September 2018) - Stowell, Alison F.; Brigham, Martin
Abstract : Purpose: In the context of the environmental impacts caused due to the increasing volumes of discarded technologies (e-Waste), this paper aims to critically evaluate whether environmental policy, the Waste of Electronic and Electrical Equipment (WEEE) legislation in particular can contribute to a shift in logic from neoliberal growth to green growth. Design/methodology/approach: Drawing upon empirical research, this paper shows how three computer waste organisations evolve through the imbrication of pre- and post-policy logics in collaborative and heterogeneous ways to create an "economy of greening". Findings: Extending the concept of a fractionated trading zone, this paper demonstrates the heterogeneous ways in which computer sourcing is imbricated, providing a taxonomy of imbricating logics. It is argued that what is shared in a fractionated trading zone is a diversity of imbrications. This provides for a nuanced perspective on policy and the management of waste, showing how post-WEEE logics become the condition to continue to pursue pre-WEEE logics. Research limitations/implications: This research focuses on three organisations and the EU 2003 and UK 2006 versions of the WEEE legislation. Practical implications: The research findings have important implications, more specifically, for how e-Waste policy is enacted as an "economy of greening" to constitute managerial and organisational adaptation needed to create a sustainable economy and society. Originality/value: This paper's contribution is threefold. First, theoretically, the literature on trading zones and imbrication is extended by considering how they can complement one another. Our focus on imbrication is a "zooming in" on the managerial and organisational implications and dynamics of a trading zone. Second, the literature on imbrication is added to by identifying a diverse range of imbricating logics that can be used to discern a more nuanced understanding of the translated effects of policy. Last, these ideas are ground in a relevant empirical context – that of e-waste management in the UK, providing a deeper knowledge, over time, of specific actors' translations of policy into organisational practices.